2018
DOI: 10.3892/ol.2018.9496
|View full text |Cite
|
Sign up to set email alerts
|

A gene mutation in RNA‑binding protein 10 is associated with lung adenocarcinoma progression and poor prognosis

Abstract: RBM10 regulates the expression of various genes, which are often mutated in male lung adenocarcinoma. The present study confirmed the association of the RBM10 mutation at exon 10 with the clinicopathological data and prognosis of lung adenocarcinoma. The effect of mutant RBM10 on regulating lung cancer cell growth and invasion was investigated in vitro. Tissue specimens from 50 patients with lung adenocarcinoma were subjected to Sanger sequencing for RBM10 exon 10 mutations. Lung adenocarcinoma cells were tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…In addition to TARP syndrome, somatic mutations in the RBM10 gene occur in numerous cancers, including lung adenocarcinoma [84][85][86][87] , colorectal cancer 88 , pancreatic cancer 89 and bladder cancer 90 . Consistent with context-specific functions of RBPs in cancer, RBM10 can function as a tumour suppressor or an oncogene [91][92][93] , possibly linked to expression of alternatively spliced variants and cross-regulatory feedback loops with the related protein RBM5 (ref.…”
Section: Mutations In Gene-specific and General Rna Processing Factors: Rbm10 And Prp8mentioning
confidence: 99%
“…In addition to TARP syndrome, somatic mutations in the RBM10 gene occur in numerous cancers, including lung adenocarcinoma [84][85][86][87] , colorectal cancer 88 , pancreatic cancer 89 and bladder cancer 90 . Consistent with context-specific functions of RBPs in cancer, RBM10 can function as a tumour suppressor or an oncogene [91][92][93] , possibly linked to expression of alternatively spliced variants and cross-regulatory feedback loops with the related protein RBM5 (ref.…”
Section: Mutations In Gene-specific and General Rna Processing Factors: Rbm10 And Prp8mentioning
confidence: 99%
“…By binding to small nuclear ribonucleoprotein (snRNPs) and cleavage sites of pre-mRNA substrates, RBM10 can synergistically remove introns and increase exon jumping events by more than 74% ( 23 , 24 ). The change in RBM10 abundance and activity can lead to changes in some gene splicing patterns and the occurrence of many diseases, such as LUAD ( 25 ).…”
Section: Alternative Splicingmentioning
confidence: 99%
“…The studies reviewed here have shown that deletion or mutation of RBM10 is associated with the occurrence and poor prognosis of human cancers, including lung and pancreatic cancer ( 6 , 34 ). For example, RBM10 mutation is significantly associated with the American Joint Committee on Cancer (AJCC) stage diagnostics, lymph node metastasis, and male patients, but not with smoking, age, tumor size, or differentiation ( 25 ). Mutations in exon 10 of RBM10 can significantly promote the proliferation and invasion of tumor cells, and the 5-year survival rate of patients with these mutations was significantly lower than that observed in healthy individuals (36.4 vs .…”
Section: Clinical Significance Of Rna-binding Motif Protein 10mentioning
confidence: 99%
See 2 more Smart Citations